Penerapan Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Operasi Teknik Kimia - Ajeng Fitri Kusumawardani; Muhammad Anwar; Nashrah Suryani (Celebes Science Education, 2024)
This study aims to improve students learning outcomes of XII Industrial Chemistry 1 Rembang State Vocational High School through learning Problem Based Learning model for Chemical Engineering Operations subject. This research is a classroom action research (PTK) to improve students learning outcomes. The method used is a discussion with TPACK-scientific approach. Data analysis in this reasearch is based on Descriptive Statistics analysis with percentage. Technique of collecting data is done by written test, questionnaire, and observation. This research conducted in three cycles. The results of this study showed an increase in learning achievement is marked by the increase of learners whose value reaches the minimum completeness criterion as a whole. In the first cycle is 61,76% or as many as 21 students achieve the minimum completeness criteria. On the second cycle there an increase achieve the minimum completeness criteria is 73,52% or as many mas 25 students. Third cycle increased the minimum completeness criteria is 94,11 % or as many as 32 students achieve the minimum completeness criteria. So, it concluded that Problem Based Learning Models can improve students learning outcomes of XII Industrial Chemistry 1 Rembang State Vocational High School for Chemical Engineering.